Discussions of Unusual Topics in Fibromyalgia - Wilke, William S. (IntechOpen, 2018)
This book is a compilation of chapters, of which two chapters review the treatment strategies for fibromyalgia syndrome (FMS), and one chapter describes the role of mitochondrial dysfunction and related pathology in the FMS pathogenesis and reviews the appropriate treatment moieties. This book chapter reviews the phenotypic changes that alter the diagnostic criteria and disease activity measures when FMS is comorbid in three potentially painful selected rheumatic diseases. The introductory preface takes the form of an editorial in which I challenge the concept that inflammation, measured as cytokine activity, plays a prominent role in the FMS pathogenesis. All of these chapters and the Preface are authoritative and accomplished discussions that provide novel perspectives on rarely addressed FMS topics.